Development of an Electronic Module Assisted by the Metaverse to Support Contextual Learning in the Geography Subject - Muhamad Rafli Tegar Hati; Alfi Sahrina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The type of research used was Research and Development (R&D), which aimed to produce and develop a metaverse-assisted electronic module that is feasible and practical to support contextual learning. The ADDIE development model was used in this study, consisting of five main steps: analysis, design, development, implementation, and evaluation. The results of the material expert validation showed an average percentage score of 90% with the criterion of very feasible, and the results of the media expert assessment produced an average percentage score of 75% with the criterion of feasible to be tested. The assessment results from students showed that the Electronic Module Assisted by the Metaverse achieved an average of 89.1% on the criterion of very practical, and the teacher assessment results showed an average of 89.5% on the criterion of very practical after testing. Based on the data obtained, the Electronic Module Assisted by the Metaverse met the criteria for validity and practicality to support contextual learning in the atmospheric dynamics material and can be used directly and independently by users.